Exploring Dementia Supporter Activities in Japan: A Review of Current Status and Issues - Kudo, Setsumi; Hamahata, Akiko; Yamasaki, Akiko; Takai, Itsushi (Recent Updates in Disease and Health Research Vol. 6, 2024)
Introduction: It is anticipated that more than 13 million dementia supporters will have undergone training by 2020. However, studies have shown that approximately 70% of patients are still inactive. Purpose of Research: This study aimed to elucidate and address the challenges associated with supporter activities for dementia. Methods: Published literature from 2015 to 2021 was collected by searching the Journal of Health Care and Society web versions. A total of 11 studies met our inclusion criteria. Results: Supporters’ ages ranged from teenagers to those in their 80s. The most active supporters were women in their 60s or older. Among them, 40%–50% had experienced caring for family members. They usually engaged in support activities alongside their jobs and housework. Support activities mainly include watching and interacting with older adults with dementia. Furthermore, they faced challenges and difficulties, such as time constraints, physical limitations, and concerns about privacy protection, in preparing meals, running errands, and accompanying older adults with dementia to outings. The leading reasons for inactivity were a lack of contact with seniors, insufficient opportunities for support activities despite high motivation, and poor self-confidence in nursing care skills and knowledge. The supporters hoped to learn appropriate care methods to manage wandering, anxiety, and delusions among older adults with dementia. Conclusion: Three significant issues have emerged. First, women aged 60 years old and older play a crucial role in supporting activities assisting older adults with dementia. Second, supporters encountered challenges, such as time constraints, physical limitations, and concerns about privacy protection during their activities. Finally, supporters seek to acquire knowledge and care skills to address the behavioral and psychological symptoms of dementia.